Validation of MicroRNAs (miRNAs) in the Early Diagnosis and Treatment of Hepatocellular Carcinoma (HCC) - Khalid, Iqra; Quraishi, Azra; Fiaz , Freeha (BioScientific Review, 2021)
Late diagnosis and delayed presentation of HCV is among the leading causes of liver cancer. MicroRNAs (miRNAs) are non-coding molecules involved in the regulation of a variety of functions happening in the cell, in both healthy and diseased states. Dysregulation of miRNAs is observed in different diseases, especially in liver cancer including hepatocellular carcinoma (HCC). The available detection methods detect HCC at a late stage. There is a need to find novel biomarkers for the diagnosis of HCC at an early stage in order to minimize the chances of liver cancer. Circulating miRNAs are novel and minimally invasive markers used for the early detection of HCV based HCC. In this review, the current progress on the potential role of miRNAs as biomarkers used for the detection of HCC and other therapeutic targets was summarized. We concluded that the expression of miRNAs is upregulated in the patients of HCC as compared with healthy individuals. An in-depth study of miRNAs as genetic biomarkers in the patients of HCC will improve its diagnosis. It will also improve the prognosis of early stage HCC patients. Furthermore, it will also help to identify a suitable and effective therapeutic target so as to reduce the chances of the failure of chemotherapy. Keywords: biogenesis, biomarkers, hepatocellular carcinoma (HCC), microRNAs (miRNAs), mRNA Copyright (c) Iqra Khalid, Azra Quraishi, Freeha Fiaz